Structured observation as a tool for reflection on teaching and learning social science subjects at primary and secondary schools with emphasis on effective use of didactic media - Labischová, Denisa (Civilia, 2020)
The study explains the significance of structured observation in the reflection on teaching and learning social science subjects at primary and secondary schools, with emphasis on effective use of didactic media. Attention is paid to visual, audiovisual, text and graphic media and their didactically structured analysis and interpretation. The author suggests criteria which can be included into an observation record sheet and which cover a broad spectrum of activities inciting higher cognitive processes and critical thinking, and also other teaching forms and methods, learning tasks, productive and creative activities, and elements of experiential education. The suggested tool is applicable in pre-gradual teacher training as part of continual teaching practice, but can also be used by aspiring teachers who enter the teaching profession, by their mentors, and other educators participating in the day-to-day operation of a particular school.
Keywords: Social science didactics; Structured observation; Didactics media; Reflection on teaching and learning